Is Attar's Fotovvatname in Istanbul ... ? - Ceylan, Ömür (Ahmet Yesevi Univ, Mutevelli Heyet Baskanligi, Taskent Caddesi 10 Sok Nu 30, Bahcelievler, Ankara 06490, Turkey, 2013)
Farid ud-Din Attar, one of the prominent and leading poets of Eastern literature, still keeps researchers busy not only with the valuable works he has left, but also with the numerous works doubtfully belonging to him. Fotovvatname of Attar is one of these works, which has provoked deliberations concerning authorship for nearly a century. Spanning from Germany to Pakistan, these lengthy deliberations have encompassed the copies existing in Turkey, Iran and Romania, but poets such as Hatifi of Hargird and Izzi-i Mervi, and scholars such as Said Nefisi, Franz Taeschner and Abdulbaki Golpinarli have not yet come to a definite conclusion. By setting out from a manuscript, which is registered in Istanbul University Central Library's Persian Manuscript Collection, Number F 1288 and which has not been seen or evaluated by the above mentioned scholars, this article will bring the deliberations to a new dimension and the text cited will be published for the first time in its original script.
Keywords: classical literature; fotovva; fotovvatname; attar; akhi; manuscript; critical edition; klasik edebiyat; ıtır; Ahi; el yazması; eleştirel basım